Investigating the Role of Symbolic Elites in Shaping Public Discourse: A Case of Detikcom - Raudy Gathmyr, Mohammad; Bre Aulia Surenggo, Muhammad (KnE Social Sciences, 2022)
Public discourse in the mass media following the political contestation of the 2017 DKI Jakarta Governor election made the Islamic Defenders Front (Front Pembela Islam) become more popular in Indonesia. FPI had a central role in the victory of the candidates it supported: Anies Baswedan and Salahuddin Uno. Considered by some as one of the most influential Islamic mass organizations in post-Reformation Indonesia, especially since 2016 after organizing a demonstration event known as the 212 Demo Action, with various pros and cons surrounding it, FPI is a social movement phenomenon that is highly and widely debated in various circles. As a ’media-darling’ (in its negative sense), it is interesting to highlight in this context how the mass media construct news stories for FPI and its leaders. Employing the critical discourse approach of ideological square and symbolic elites from Teeun A van Dijk, this paper examines how one of the largest mainstream media organizations in Indonesia, Detikcom, ’mediates’ discourse about FPI through its reporting. Keywords: symbolic elites, CDA, FPI, Indonesia